2021
DOI: 10.1007/s11172-021-3303-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structures of 4,5-dimethyl-1,3-bis(pyridin-2-ylmethyl)-1H-imidazolium chloride and 1,1′-bis(pyridin-2-ylmethyl)-2,2′-bis(4,5-dimethylimidazole)

Abstract: 4,5-Dimethyl-1,3-bis(pyridin-2-ylmethyl)-1H-imidazolium chloride (1) was synthesized and characterized by IR and NMR spectroscopy and X-ray diff raction. An attempt to prepare the free tridentate N-heterocyclic carbene pincer ligand by the reaction of 1 with KN(SiMe 3 ) 2 resulted in the formation of 1,1´-bis(pyridin-2-ylmethyl)-2,2´-bis(4,5-dimethylimidazole) as a product of dimerization of the target carbene followed by the rearrangement accompanied by the elimination of dipyridylethane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 60 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…67 Previously we have demonstrated that the isolation of a free carbene after deprotonation of 4,5-dimethyl-1,3-bis(2-pyridylmethyl)-1Himidazolium chloride (1) with KN(SiMe 3 ) 2 is difficult because of its fast dimerization in solution. 68 In the present study the precursor of pincer-type NHC ligand 1 was reacted directly with bis(amido) compounds [(Me 3 Si) 2 N] 2 M(THF) 2 (M = Ca(II), Yb(II)) in a 1:2 molar ratio in toluene at room temperature (Scheme 1) to afford heteroleptic M(II) bis-(amido) NHC complexes 2 and 3. The process most likely involves a series of transformations: deprotonation of the imidazolium salt by [(Me 3 Si) 2 N] 2 M(THF) 2 ; coordination of the formed NHC to [(Me 3 Si) 2 N] 2 M(THF) 2 ; proton abstraction from the rater acidic methylene group of the picolyl fragment by N(SiMe 3 ) 2 − anion; dearomatization of one of the pyridine rings, and formation of exocyclic C�C and covalent M−N pyridyl bonds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…67 Previously we have demonstrated that the isolation of a free carbene after deprotonation of 4,5-dimethyl-1,3-bis(2-pyridylmethyl)-1Himidazolium chloride (1) with KN(SiMe 3 ) 2 is difficult because of its fast dimerization in solution. 68 In the present study the precursor of pincer-type NHC ligand 1 was reacted directly with bis(amido) compounds [(Me 3 Si) 2 N] 2 M(THF) 2 (M = Ca(II), Yb(II)) in a 1:2 molar ratio in toluene at room temperature (Scheme 1) to afford heteroleptic M(II) bis-(amido) NHC complexes 2 and 3. The process most likely involves a series of transformations: deprotonation of the imidazolium salt by [(Me 3 Si) 2 N] 2 M(THF) 2 ; coordination of the formed NHC to [(Me 3 Si) 2 N] 2 M(THF) 2 ; proton abstraction from the rater acidic methylene group of the picolyl fragment by N(SiMe 3 ) 2 − anion; dearomatization of one of the pyridine rings, and formation of exocyclic C�C and covalent M−N pyridyl bonds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The latter method is often used for the synthesis of alkaline earth and rare earth complexes with functionalized NHCs. , Moreover, divalent lanthanide and alkaline earth complexes supported by NHC ligands can be obtained by a redox-transmetalation reaction using air-stable AgI–NHC complexes, although this method is more common in late transition metal chemistry . Previously we have demonstrated that the isolation of a free carbene after deprotonation of 4,5-dimethyl-1,3-bis­(2-pyridylmethyl)-1 H -imidazolium chloride ( 1 ) with KN­(SiMe 3 ) 2 is difficult because of its fast dimerization in solution . In the present study the precursor of pincer-type NHC ligand 1 was reacted directly with bis­(amido) compounds [(Me 3 Si) 2 N] 2 M­(THF) 2 (M = Ca­(II), Yb­(II)) in a 1:2 molar ratio in toluene at room temperature (Scheme ) to afford heteroleptic M­(II) bis­(amido) NHC complexes 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations